Pengembangan Sikap Keberagamaan Peserta Didik Era 4.0 - Majdudin Nurul Huda (Tihamah: Jurnal Studi Islam, 2023)
In the last decade, the world of education in Indonesia has faced major challenges regarding student safety in schools. The challenge in question is a crisis of student morality or character which is marked by the increasing phenomenon of violence in schools or what is generally known as bullying. This case of bullying occurs because they can show their true identity which might be considered something "cool" just in a disclosure given to them. This is because students' emotional levels are still unstable, so this behavior is often carried out by students. This incident can be seen from the development of religious attitudes held by those who promote their beliefs which are still weak. This research includes library research, therefore the steps that will be taken are exploration of a number of data from various literature, both primary data and secondary data. This religious development attitude needs to be arranged in such a way that students can explore these religious attitudes which will later be implemented with positive, not negative, attitudes. This religious experience must always be embedded and carried out for better changes in attitudes.